Can teacher-child relationships alter the effects of early socioeconomic status on achievement in middle childhood?. (October 2017) - McCormick, Meghan P.; O'Connor, Erin E.; Parham Horn, E.
Abstract: Using data from the NICHD SECCYD ( N  = 1053), we used two-level hierarchical linear models with site fixed effects to examine whether teacher-child closeness and conflict moderated associations between two indicators of early socioeconomic status (maternal education and family income) and standardized measures of children's math and reading achievement at 54 months, 1st, 3rd, and 5th grades. Children whose mothers had lower levels of education and conflictual relationships with teachers exhibited lower reading achievement, on average, across elementary school. At the same time, children with less educated mothers who experienced increases in teacher-child closeness and decreases in teacher-child conflict exhibited improvements in reading achievement across elementary school. Finally, low teacher-child closeness elevated the risk for poor math achievement posed by low family income. Implications for intervention design and development are discussed.